Analisis Nilai-Nilai Pendidikan Islam Dalam Perspektif Al-Qur’an Surat Luqman Ayat 13-19 - Rahmi, Natasya Alfany; Fauziah, Debibik Nabilatul; Ulya, Neng (Peneliti.net, 2024)
Education is a very important issue for all groups. Education has always been the foundation, the hope for developing individuals and society. Education will advance civilization, develop society and create a generation capable of doing much for their interests, or in other words, education can actually be understood as a series of renewal efforts. Education essentially knows no differences. Education can be interpreted as a process of changing the behavior of children so that they become adult humans who are able to live independently and as members of society in the natural environment around which the individual lives. Education does not only include intellectual development, but more emphasis is placed on the process of forming and developing a person's personality, including children and students as a whole, so that they become more mature. So education is a structured process of changing human thought patterns. The aim of this research is to find out the interpretation contained in the Al-Qur'an Surah Luqman verses 13-19 and to find out the analysis of the values of Islamic education from the perspective of Q.S Luqman verses 13-19. The approach to this research is qualitative with library research methods. Based on the results of the analysis of the Al-Misbah tafsir, Al-Azhaar tafsir, Ibnu Katsir's tafsir, the educational values found in the Al-Quran Surah Luqman verses 13-19 are moral education, Aqidah education, and sharia education. Moral education is education that seeks to introduce, instill and make children aware of the existence of a value system that regulates human patterns, attitudes and actions on earth. Aqidah education is education that seeks to introduce, instill and convey to children the values of belief in the pillars of faith and other things like that. Sharia education is sharia education which seeks to introduce, instill and make children aware of the values of God's regulations regarding the procedures for regulating human life behavior, whether related vertically to God which is called worship.